Próby ocalenia tragedii w wieku XIX - Przybyszewska, Alicja (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The article outlines the issue of genre-transformation of tragedy in 19th-century Polish drama. The fundamental question is tragedy’s potential after liberation from the most important structural categories of the genre: the three unities, catharsis and anagnorisis. The discussion on the 19th-century patterns of tragedy, derived from contemporary theory, criticism, and theatrical production, are based on research by Marek Dybizbański, who presented an interesting analysis of the problem, which was an important indicator of contemporary literary thought, in his study called Tragedia polska drugiej połowy XIX wieku — wzorce i odstępstwa [The Polish Tragic Drama in Late 19th Century — Patterns and Divergence]. The issues discussed were: disproportion between expectations and effects, indicated by repertoires and contemporary debate on drama, lack of standard productions of tragedy, matched by great surplus of texts that tried to set the standard, and by programmatic declarations on how to do it. The author, following Dybizbański’s discussion, focuses on the question why the 19th century in Poland was, for tragedy, a lost time.